A New Inclusive Volcanic Risk Ranking, Part 2: Application to Latin America - Guimarães, Letícia Freitas; Nieto-Torres, Amiel; Bonadonna, Costanza; Frischknecht, Corine (Frontiers in Earth Science, 2021)
Volcanic Risk Ranking (VRR) methods have been developed worldwide as a way to hierarchize the volcanic systems and help target strategies for risk reduction. Such hierarchization is especially important in areas characterized by a large number of active volcanoes but limited resources. This is the case of Latin America, where large populations live nearby almost 300 active volcanoes. Here we assess the volcanic systems in Latin America with at least one eruption in the last 1,000 years based on the VRR strategy presented in a companion paper that accounts for the 4 main risk factors: hazard, exposure, vulnerability and resilience. Our results reveal that, among the 123 volcanoes analyzed, Santiaguito, Tacaná and Fuego are those with the highest score in the 3-factor VRR (H×E×V), while Ecuador, Marchena and Santiago are among the systems with the lowest score. Bárcena and Pinta score zero as there is no exposure. Although vulnerability significantly contributes to the VRR score, hazard and exposure are the main factors that define the risk of Latin American volcanic systems in the proposed 3-factor VRR, while resilience contributes to its reduction in the proposed 4-factor VRR strategy. In this regard, Arenal, Copahue, Villarrica, Ubinas, Irazú and Poás are the systems with the highest number of risk reduction strategies in place. Atitlán, Almolonga and Tecuamburro are the volcanic systems with the highest score in the 4-factor VRR [(H×E×V)/(Res+1)], combining moderate hazard, exposure and vulnerability and low resilience; Bárcena, Pinta, Ecuador, Marchena and Santiago receive the lowest scores due to no or low exposure. Santiaguito, Tacaná, El Chichón and Ceboruco are characterized by high scores in the 3-factor VRR and also stand out as some of those with few risk reduction strategies implemented; thus they have intermediate to high scores also in the 4-factor VRR. Recognizing that hazard is difficult to mitigate and reducing exposure may depend on hardly feasible relocation of infrastructure and already established communities, we emphasize that measures to reduce vulnerability and increase resilience should be promoted (e.g., creating redundancy/accessibility to infrastructure, carrying out risk assessment studies, implementing early warning systems, developing emergency plans and promoting educational activities).